XePhIR: the zebrafish xenograft phenotype interactive repository. (28th April 2022) - Groenewoud, A; Forn-Cuní, G; Engel, F B; Snaar-Jagalska, B E
Abstract: Zebrafish xenografts are an established model in cancer biology, with a steadily rising number of models and users. However, as of yet, there is no platform dedicated to standardizing protocols and sharing data regarding zebrafish xenograft phenotypes. Here, we present the Xenograft Phenotype Interactive Repository (XePhIR, https://www.xephir.org ) as an independent data-sharing platform to deposit, share and repurpose zebrafish xenograft data. Deposition of data and publication with XePhIR will be done after the acceptation of the original publication. This will enhance the reach of the original research article, enhance visibility and do not interfere with the publication or copyrights of the original article. With XePhIR, we strive to fulfill these objectives and reason that this resource will enhance reproducibility and showcase the appeal and applicability of the zebrafish xenograft model. Database URL : https://www.xephir.org